Models for paleodietary research: Three case-studies from arid and semi-arid environments in Northwest Argentina - Killian Galván, Violeta Anahí (2018)
In this article, we present three case-studies of paleodietary reconstruction from Prehispanic agropastoralist societies located in the arid and semi-arid zones of North western Argentina. These three examples include the micro-region of Antofagasta de la Sierra, located in the puna of the Catamarca Province; the puna archaeological site of Río Doncellas; and the pre-puna archaeological site of Los Amarillos. These latter two sites are situated in the Jujuy Province. Here we present a quantitative approximation that provides a relative hierarchy of plant versus animal resource consumption. In so doing, we aim to overcome the uncertainty generated by previous studies on this theme. To this end, we employed the mixed Baysian model FRUITS (Food Reconstruction Using Isotopic Transferred Signals), which utilises three different proxies – δ13Ccollagen, δ13Capatite and δ15N. This model confirmed the importance of maize vis-à-vis other resources at Los Amarillos, its lesser relevance within the Antofagasta de la Sierra context, and its negligible presence at the Río Doncellas site. Likewise, within the resource hierarchy of the puna economy – Solanum tuberosum – a seemingly, marginal crop, in contrast to camelids, gained greater traction. In this manner, we can detect the different nutritional strategies employed by the Prehispanic agropastoralist economies of the region.